Why Deprescribing Instead of Not Prescribing? - Welma Wildes Amorim; Luiz Carlos Passos; Marcio Galvão Oliveira (Brazilian Society of Geriatrics and Gerontology, 2024)
Prescribing medications involves complex cognitive processes, and mistakes in prescription can cause serious adverse events. Deprescribing is one of the last opportunities to prevent patient harm from the use of drugs that should be avoided, especially among older patients. This viewpoint article aims to discuss the prescription process and some essential concepts, such as polypharmacy, prescription of potentially inappropriate medications, and, particularly, the relevance of deprescribing and its relationship with the appropriate prescription of medications in older people.